Relative Humidity Sensor Based on Microfiber Loop Resonator - Yangzi Zheng; Xinyong Dong; Chunliu Zhao; Yi Li; Liyang Shao; Shangzhong Jin (Advances in Materials Science and Engineering)
A novel relative humidity (RH) sensor based on a microfiber loop resonator (MLR) is proposed and experimentally demonstrated. As refractive index of the microfiber in the MLR is modified by environmental humidity, resonant wavelength of the MLR changes with RH level. By detecting this wavelength shift, RH measurement is realized with a linear response sensitivity of 1.8 pm/% RH. The obvious advantage of this technique over others is that no coating of humidity-sensitive material is required.